2014
DOI: 10.1145/2601097.2601122
|View full text |Cite
|
Sign up to set email alerts
|

Eyeglasses-free display

Abstract: Figure 1: Vision correction with computational displays. On a conventional screen, people with optical aberrations see a blurred image (center left). Current approaches to aberration-correcting display use multilayer prefiltering (center) or light field displays (center right). While the former technology enhances perceived image sharpness, contrast is severely reduced. Existing light field-based solutions offer high contrast but require a very high angular sampling density, which significantly reduces image r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Other methods for reducing vergence-accommodation conflict (VAC) in VR NEDs have also been suggested, including mono-vision and the use of focus-tunable lenses ( 59 ). By distorting the image displayed, Huang et al ( 60 ) showed that correction for refractive defects may be encoded into a light field display, doing away with the need for glasses. In Chakravarthula et al ( 61 ), depth perception, peripheral awareness, eye tracking, scanning, and visual processing speed are all implemented in a simulated real-space environment to maximize the effect of the training and to create a good transference potential to real-world dynamic environment scenarios ( 62 ).…”
Section: Vr Exercises For Prevention and Control Of Human Ocular Dise...mentioning
confidence: 99%
“…Other methods for reducing vergence-accommodation conflict (VAC) in VR NEDs have also been suggested, including mono-vision and the use of focus-tunable lenses ( 59 ). By distorting the image displayed, Huang et al ( 60 ) showed that correction for refractive defects may be encoded into a light field display, doing away with the need for glasses. In Chakravarthula et al ( 61 ), depth perception, peripheral awareness, eye tracking, scanning, and visual processing speed are all implemented in a simulated real-space environment to maximize the effect of the training and to create a good transference potential to real-world dynamic environment scenarios ( 62 ).…”
Section: Vr Exercises For Prevention and Control Of Human Ocular Dise...mentioning
confidence: 99%
“…Light-field displays have also been proposed as an alternative to overcome the limitations of single-image solutions, whereby a microlens array is placed on top of the display to provide a higher degree of control over the directionality of the emitted light. Vision correction can be achieved using such displays [93][94][95] by utilizing vision simulations to prefilter the displayed images.…”
Section: Vision-correcting Devicesmentioning
confidence: 99%
“…Perhaps one of the most unconventional applications of light-field displays is the assessment 17 and correction 18 of visual aberrations in a human observer (see Fig. 4).…”
Section: Assessing and Enhancing Human Visionmentioning
confidence: 99%
“…Ignoring stereo cues and motion parallax, however, allows for practical light-field displays to be built that support only focus cues. 17,18 To assess visual aberrations, a light field containing a pair of lines can be presented to an observer such that the retinal projections exactly overlap when the viewer has normal or corrected vision but appear at spatially distinct locations when that is not the case. By interactively aligning the lines, one can manually pre-distort the light field until the pre-distortions are canceled out by the refractive errors of the eye.…”
Section: Assessing and Enhancing Human Visionmentioning
confidence: 99%